(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Chronic hepatitis B is a disease of global burden. Variable range of presentations and different phenotypes has made the disease unique and produces difficulties in diagnosis of the disease. This study aimed to identify the varying clinical presentation and phenotype of chronic hepatitis B in children. Materials and methods: This cross-sectional observational study was conducted at Paediatric Gastroenterology and Nutrition Department in BSMMU, Dhaka, Bangladesh, from January, 2018 to June 2019. Total 70 children of chronic hepatitis B were studied. Detailed history, clinical examinations and investigations such as CBC, liver function test, HBsAg, HBeAg, Anti HBe Hepatitis B virus DNA were done for all patients. Their phenotypes were determined. Results: Among total 70 patients about half of the patients were in the older age group and (68.6%) were male. Clinically about (68.57%) were asymptomatic. Among the symptomatic patients common presentations were anorexia/nausea/vomiting (28.6%), abdominal pain (27.1%), hepatomegaly (12.8%), jaundice (10.0%), Spleenomegaly (5.72%). Majority of them were biochemically normal. Serum ALT and S. AST was raised only in (34.3%) and (31.4%) respectively. HBeAg was positive in (61.4%) patients. Phenotypic presentation revealed immune tolerant 45.7%, immune active 20.0%, inactive carrier 20.0%, another 14.3% patients were in the HBeAg negative phase. Conclusion: Majority of the children with chronic hepatitis B were clinically asymptomatic, biochemically normal and phenotypically in the immune tolerant phase. But an important number of children showed feature of active hepatitis Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 42-46